GUARANTEES OF THE LOYALTY OF PROVIDING PUBLIC SERVICES IN UKRAINE:: LEGAL AND SOCIAL ASPECTS - Leheza, Yevhen; Deliya, Yuriy; Ryzhkov, Eduard; Albul, Serhii; Iliushchenko, Hanna (Revista Gênero e Interdisciplinaridade, 2020)
The scientific article is devoted to the coverage of guarantees of public services loyalty in Ukraine. It is proposed to include the following types of guarantees to ensure the loyalty of public services in Ukraine: appeals of decisions, actions or inactions of public administration entities on the provision of public services in court (administrative proceedings); control over the activities of public administration entities on the provision of public services; appeals of individuals (citizens and stateless persons) in accordance with the Law of Ukraine "On Appeals of Citizens"; bringing public servants to responcibility for refusing to provide a certain type of public service. It is established that the significance of legal guarantees of loyalty of public services provision lie in: assurance of the rights and freedoms of a human and a citizen in the process of obtaining various public services; compliance with international human rights standards in the field of public services; improving the state image represented by subjects of these services; etc